UKURAN PERUSAHAAN SEBAGAI PEMODERASI PENGARUH PROFITABILITAS DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR - Muliantari, Ni Putu Indah Ayu; Latrini, Made Yenni (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of profitability and financial distress to the audit delay in manufacturing companies with the size of the company as a moderating. This study was performed on companies listed in Indonesia Stock Exchange during the period 2013-2015. Secondary data collection methods, namely by looking at the data necessary in the audited financial statements of the company. The number of samples obtained as many as 156 samples using purposive sampling method of sampling. Data have fulfilled classical assumption test, data analysis technique used is Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA) with SPSS software. The results of this study stated that profitability and financial distress effect on audit delay. The size of the company is not able to moderate the effect of profitability audit delay but able to moderate the effect of financial distress audit delay.
Keywords: Keywords: Audit Delay, Company Size, Profitability, Financial Distress